Why Canoes? An Exhibit at the University of Minnesota’s Northrop Gallery - David Morrison (Open Rivers: Rethinking Water, Place & Community, 2021)
Minnesotans love boats, and canoes are a particular favorite. The state has the highest per capita rate of recreational boat ownership in the nation, according to the Department of Natural Resources.[1] Consequently, the current exhibit, Why Canoes? Capacious Vessels and Indigenous Future of Minnesota's Peoples and Places, at the Northrop Gallery should find an interested audience. The exhibit reflects the desire of three Indigenous peoples—Dakota, Anishinaabe, and Micronesian—to revitalize their canoe-building traditions, and to pass them on to the next generation.